Features of Implementation of the Modified "up-and-down" Method - Krūmiņš, K.; Pētersons, V.; Plociņš, V. (Elektronika ir Elektrotechnika, 2009)
There is described the modified "up-and down" method and illustrated the advantages of the said method in comparison with thestandard "up-and-down" method. The modified method is not critical in selection of the step size of the threshold changing. Theautocorrelation feature of the converted noise is used for decreasing the amount of averaged values. There is given the flowchart of thepractical implementation of the modified method to be used in discrete stroboscopic converters. Ill. 7, bibl. 6 (in English; summaries inEnglish, Russian and Lithuanian).